The Effect of Additional Employee Income (TPP) and Work Ability on Employee Performance at the Regional Civil Service Office of North Morowali Regency - Riski Alivia; Andi Indriani Ibrahim; Yoberth Kornelius; Nur Riski Isliansty (Universitas Muhammadiyah Palu, 2026)
This study aims to analyze the effect of Employee Income Supplement (TPP) and Work Ability on Employee Performance at the Regional Civil Service Agency (BKD) of North Morowali Regency, both simultaneously and partially. The background of this research is based on the phenomenon of suboptimal employee performance, characterized by low work quality, late completion of tasks, and low employee initiative and independence. This research is a descriptive quantitative study using a survey questionnaire. The sampling technique used saturated sampling with 46 respondents. Data were analyzed using multiple linear regression, including validity and reliability tests, classical assumption tests, and hypothesis tests. The results indicate that Employee Income Supplement (TPP) and Work Ability simultaneously have a significant effect on Employee Performance. Partially, each independent variable, namely TPP and Work Ability, also has a significant effect on performance. These findings indicate that increasing performance-based incentives and improving employee abilities, both intellectually and physically, can drive improved employee performance